Kandungan Magnesium, Kalium, Kalsium Dan Fosfor Pada Produk Pangan Dari Tepung Biji Durian - Irwan Said; Baharuddin Hamzah; Jamaluddin Sakung; Purnama Ningsih; Poppy Fitra Wahyuni; Rezki Rezki (Media Eksakta, 2023)
Durian seed flour can be used for the manufacture of food products such as sticks and steamed sponges. Sticks and steamed sponge cake are foods that many people like from children to adults.  Durian seed flour is rich in minerals including magnesium, potassium, calcium and phosphorus. This study aims to determine the content of magnesium, potassium, calcium and phosphorus in food products from durian seed flour using Atomic Absorption Spectrophotometer (SSA) and UV-Vis Spectrophotometry.   The results showed that the magnesium content in the sticks of durian seed flour with formulation 1 (0% durian seed flour) amounted to 84,053 mg/kg, formulation 2 (50% durian seed flour) amounted to 145,213 mg/kg and formulation 3 (100% durian seed flour) amounted to 142,313 mg/kg.  Potassium content on sticks from durian seed flour with formulation 1 (0% durian seed flour) of 1,186 mg/kg, formulation 2 (50% durian seed flour) of 1,863 mg / kg and formulation 3 (100% durian seed flour) of 1,693 mg/kg.  The calcium content in steamed sponge from durian seed flour with formulation 1 (0% durian seed flour) of 30.37 mg/kg, formulation 2 (50% durian seed flour) of 37.84 mg/kg and formulation 3 (100% durian seed flour) of 35.84 mg /kg. While the phosphorus content n steamed sponge from durian seed flour with formulation 1 (0% durian seed flour) of 17.1 mg/kg, formulation 2 (50% durian seed flour) of 27.1 mg/kg and formulation 3 (100% durian seed flour) of 24.3 mg/kg.